(untitled) (Ictus, 2022)
Abstracts of the first joint annual meeting "ictus2021" of the "Asociación Mexicana de Enfermedad Vascular Cerebral (AMEVASC)" and the " Sociedad Iberoamericana de Enfermedades Cerebrovasculares (SIECV)" in October 2021.